Complications of Neck Dissection in Head and Neck Cancer: A 5-Year Retrospective Analysis of Incidence and Risk Factors at a Libyan Tertiary Center - Ayad Alkhalifi; Nagia Bengharbia; Mustafa Zaneen; Nagah Majdoub (AlQalam Journal of Medical and Applied Sciences, 2025)
Neck dissection is integral to head and neck cancer management but carries significant morbidity, particularly in resource-limited settings where advanced presentations prevail. This study analyzes complication rates and risk factors following neck dissection at a Libyan tertiary center to guide context-specific surgical protocols. A 5-year retrospective analysis of 37 patients undergoing neck dissection (2017–2021) was conducted. Complications were classified by type, timing, and Clavien-Dindo severity. Multivariate regression identified risk factors. The cohort (mean age 56.2±10 years; 59.5% male) demonstrated a 40.5% complication rate, with infections (18.9%) and nerve injuries (16.2%) predominating. Modified radical neck dissection (MRND) had the highest infection rate (33.3% vs. 8.3% for selective dissection, p=0.031). Independent risk factors included advanced age (OR=2.3, 95%CI:1.2–4.4) and MRND/radical procedures (OR=3.5, 95% CI:1.3–9.2). Complication rates exceed global benchmarks, underscoring the need for targeted interventions: infection control in MRND, nerve preservation training, and preoperative optimization for elderly patients.